University - School Interface: pedagogical innovations based on the development of a MOOC on Socio - Scientific Issues (CSC) as a didactic strategy - Beltrán Penagos, María Alejandra; Gutiérrez Verano, Katherin Alexandra; Martínez Pérez, Leonardo Fabio; Ramírez Martínez, Jorge Enrique (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2017)
This article presents the results of an educational experience of ongoing teacher training, developed with in-service teachers belonging to the capital district, based on the theory of connectivism and supported in the development of a "MOOC" on socioscientific issues as a didactic strategy. The pedagogical, didactic and digital characteristics that articulated the social networks and audiovisual resources housed in Google's G + platform are related here and synchronously and asynchronously show the potential of the University - School interface.